Detection of Bacterial Contamination of Syrian Paper Currency Circulating in some Broiler Stores in Lattakia (Latakia University Journal -Biological Sciences Series, 2020)
The research aims to detect the bacterial contamination of Syrian Paper Currency which is used in some stores that sell live orslaughtered chicken in several neighborhoods of the city in Lattakia, Out of 120 samples from the different categories of paper currency (2000 Syrian pounds, 1000 S.P, 500 SP, 200 SP, 100 SP, 50 SP), 139 bacterial isolates were obtained, of which / 83 / a pure colony of bacilli are negative for Gram stain and / 56 / a pure colony of cocci included positive staphs for Gram stain, The results showed the bacterial contamination of all 100 samples with 100% contamination. The Api Staph  kit was applied to identify 7 different species of the staphylococcus Coccus including: Staph intermedius (14.2%) and Staph. Xylosus (8.9%), Staph. aureus (19.6%) Staph. epidermidis (14.2%), Staphy. capitis (16.1%), Staph. Lentus (16.1%) Staph yugdunensis (10.7%) . 8 types of intestinal familywere identifiedusing API 20E, these types included: Escherichia coil (26.5), Pasteurella pneumoniae (13.2%), Citrobacter freundi (13.2%), Salmonella typhi (9.6%) Salmonella, enteric (6%), Klebsiella ornithinolytica (10.8%), Proteus spp. (4.8%) in addition to two types of the pseudo-family, Pseudomnas aeruginosa (7.2%), Pseudomnas luteola (8.4%), and the percentage of Gram-negative bacteria was greater (59.7%) compared to the positive bacteria of the Gram stain (40.2%). Also the low Paper Currency (50–100–200-500)  were more contaminated than high Paper Currency, while it was found that there were significant differences between the numbers of bacteria isolated from the paper currency between live and slaughtered broilers. The results of the statistical analysis showed that there were significant differences between the numbers of bacteria isolated from the air of the stores in the live chickens. Slaughtered broiler stores 42 ± 0.48 bacterial cells / m3.